The functional role of p38 MAPK pathway in malignant brain tumors - Grave, Nathália; Scheffel, Thamiris Becker; Cruz, Fernanda Fernandes; Rockenbach, Liliana; Goettert, Márcia Inês; Laufer, Stefan; Morrone, Fernanda Bueno (Frontiers in Pharmacology, 2022)
Gliomas are extremely debilitating malignant brain tumors with very limited response to therapies. The initiation and progression of gliomas can be attributed to several molecular abnormalities, such as mutations in important regulatory networks. In this regard, the mitogen-activated protein kinases (MAPKs) arise as key signaling pathways involved in cell proliferation, survival, and differentiation. MAPK pathway has been altered in most glial tumors. In glioma cells, the activation of p38 MAPK contributes to tumor invasion and metastasis and is positively correlated with tumor grade, being considered a potential oncogenic factor contributing to brain tumorigenesis and chemotherapy resistance. Hence, a better understanding of glioma pathogenesis is essential to the advancement of therapies that provide extended life expectancy for glioma patients. This review aims to explore the role of the p38 MAPK pathway in the genesis and progression of malignant brain tumors.